2021
DOI: 10.3389/fcell.2020.619924
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α/BNIP3-Mediated Autophagy Contributes to the Luteinization of Granulosa Cells During the Formation of Corpus Luteum

Abstract: During the luteinization after ovulation in mammalian ovary, the containing cells undergo an energy consuming function re-determination process to differentiate into luteal cells under avascular environment. Previous evidences have delineated the contribution of autophagy to the cell differentiation and the catabolic homeostasis in various types of mammalian cells, whereas few interest had been focused on the involvement of autophagy in the luteinization of granulosa cells during the formation of early corpus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…In the ovary, autophagy has been associated with follicle development and atresia as well as luteal formation and regression [ 174 , 176 , 214 , 215 , 216 , 217 , 218 , 219 ]. Recently, Tang et al (2020) found that HIF1α enhances autophagy in the rat luteinized granulosa cells [ 217 ].…”
Section: Metabolic Events Induced By Lh In the Corpus Luteum: The Crosstalk Of Pka/mtor And Ampk Signaling In The Regulation Of Metabolicmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ovary, autophagy has been associated with follicle development and atresia as well as luteal formation and regression [ 174 , 176 , 214 , 215 , 216 , 217 , 218 , 219 ]. Recently, Tang et al (2020) found that HIF1α enhances autophagy in the rat luteinized granulosa cells [ 217 ].…”
Section: Metabolic Events Induced By Lh In the Corpus Luteum: The Crosstalk Of Pka/mtor And Ampk Signaling In The Regulation Of Metabolicmentioning
confidence: 99%
“…In the ovary, autophagy has been associated with follicle development and atresia as well as luteal formation and regression [ 174 , 176 , 214 , 215 , 216 , 217 , 218 , 219 ]. Recently, Tang et al (2020) found that HIF1α enhances autophagy in the rat luteinized granulosa cells [ 217 ]. HIF1α is highly expressed in the granulosa cells of preovulatory follicles in various species [ 220 ].…”
Section: Metabolic Events Induced By Lh In the Corpus Luteum: The Crosstalk Of Pka/mtor And Ampk Signaling In The Regulation Of Metabolicmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF‐1α, furthermore, is also an inductor for mitophagy 15 . The cells have been undergone hypoxia in the mitochondria; HIF‐1α can be activated and/or promotes cell death through its downstream elements Bcl‐2/E1B interacting protein 3 (BNIP3) or BNIP3L (NIX), disturbing the interaction between Beclin‐1 and Bcl2 16 …”
Section: Introductionmentioning
confidence: 99%
“…In the ovary, autophagy has been associated with follicle development and atresia as well as luteal formation and regression (Escobar et al, 2008;Choi et al, 2011;Aboelenain et al, 2015;Grzesiak et al, 2018;Meng et al, 2018;Zhang et al, 2018;Tang et al, 2019;Tang et al, 2020;Wen et al, 2020). However, the signaling pathways responsible for regulation of autophagy in luteal cells have received little attention.…”
Section: Introductionmentioning
confidence: 99%